ECONOMIC IMPLICATIONS OF CURRENCY RATE FLUCTUATIONS IN INTERNATIONAL FINANCIAL MARKETS. - Sriraman V P, C T Sunilkumar, Mahesh Ramakrishna Pillai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The global business scenario is ever dynamic. The changes happening in the money market is reflected in the economic scenario through the changes in the business trends. The changes are reflected through the changes in the market trends. These changes are trying to hold the financial and business potentials more flexible and fair. The sea was worst in the past to reach nations to do business. Recognizing the unending frontiers of business across the nations, men started to conquer the many lands for business in terms of better money and better profit. To meet the unending demand for the products and services across the nations, men started dealing through diversified possibilities of business like exchange of facilities, barter system, gold / silver related commodities, etc. There aroused an agenda of disadvantages while dealing with such business across the borders. This lead to the need of a unique commodity of exchange with no much concern like the barter system, gold rates etc. lead to the innovation of currency and further advanced to introduction of other financial instruments including paper currencies and bullion exchanges. Profit is the aim of any business. Doing business against any international currencies gains much better advance to the business deals. Over a period of time nation started thinking about diversified forms of business deals through fixed and floating exchange rate of currencies and the capital gains.This introduction of multiple payment settlement system in business across borders, made global business to be the best place to look for quality product at competitive prices. This made companies and even nations to think of international business against any other business due to the profit it earns while trading in economically stabilized nations. Foreign exchange brings wealth to nations at no extra efforts. The increase in the business across borders, made nations to think in lines of a unified currency system. Economists and financial experts introduced the currency rate as the base for international business. The fixed and floating rate of currencies were introduced as diversified techniques for business settlement. Nations started thinking of This enabled the nations to fix-up a common value for the currency in which regular trading happens with another nation or to fix a regular rate with one of the balanced third world currencies. This fixed currency exchange practice enabled nations to plan the financial requirements in business. This study is mainly a concentration of research into the aspects of currency agreements in UAE against US Dollars and other GCC countries.Thus, the major concern in this is to evaluate the benefits expected through currency fixing strategy. The study throws light to factors that determine the pegging system against major currencies like US dollar, euro, Sterling Pound. Further the study tries to cover few areas of independent float and its advantages. A brief about common currency, currency board, GCC Currency etc. is touched upon as part of the study. The study further examines the various economic indicators as well as the currency fluctuations. The relative currency fluctuations over a period of time was studied with the support of statistical tools. The study gave a generalized view on the factors benefitting the pegging system of currency in international business scenario.